The Mass Balance of the Kozelsky Glacier in Kamchatka for 1977–2022 - A. Ya. Muraviev; G. A. Nosenko; I. K. Mironov; V. N. Dvigalo; Ya. D. Muraviev (Лëд и снег, 2023)
The change in the volume of the Kozelsky Glacier in Kamchatka for the period 1977–2022 (1977–2015 and 2015–2022) was estimated using historical data and modern DEM. During this period, the area of the glacier did not change much. At the same time, its length increased by about 0.7 km, while the width decreased over its almost whole extent. The volume of the glacier decreased by 34.15 ± 6.74 million m3, and its surface became lower by 17.30 m, on the average. The cumulative mass balance amounted 14.70 ± 3.94 m w.e., and the mean annual value –0.33 m w.e. yr–1. In the last 45 years, the ice loss and redistribution to lower hypsometric levels took place on the Kozelsky Glacier. In 1977–2015, the average area change in the altitude of the glacier surface was equal to –17.84 m, the volume decreased by 35.21 ± 7.20 million m3, the cumulative mass balance amounted –15.16 ± 4.17 m w.e., and the mean annual balance –0.40 m w.e. yr–1. In the period 2015–2022, an elevation of the glacier surface was recorded by 0.59 ± 1.55 m on the average, the volume increased by 1.01 ± 2.65 million m3, the cumulative mass balance amounted to 0.50 ± 1.35 m w.e., and the mean annual balance – to 0.07 m w.e. yr–1. During the last decade, a slowdown in the movement of the glacier front down the valley was recorded. In 2012–2022, the glacier front advanced with a velocity of about 5.2 m/year, while it was 17.9 m/year in 1977–2007, and 20.0 m/year in 2007–2012. The current climatic conditions are not favorable for development of glaciers. In 1977–2022, a trend of the summer air temperature rise was observed with a relatively stable amount of precipitation falling during the cold period. The almost continuous (except 1978–1981) advance of the glacier in 1977–2022 can be explained by the influence of the volcanic factor. A thick surface moraine covers more than 2/3 of the glacier area and, thus, prevents the surface ablation. Increased seismic activity associated with active volcanism promotes the ice movement.